A Review of Process Intensification Strategies in Biodiesel Production from Waste Cooking Oil to Enhance Efficiency and Sustainability - laila, Laila Rahayuningtyas; Marwah, Alyamida; Istinaroh, Siti; Nuzulaekha, Azzahra (Journal of Clean Technology, 2025)
The global energy crisis and environmental concerns from fossil fuel use have driven the development of renewable biofuels. Biodiesel produced from waste cooking oil (WCO) is a promising option due to its low cost, wide availability, and non-competition with food resources. However, WCO typically contains high levels of free fatty acids (FFA), moisture, and impurities that hinder efficient conversion. This review highlights recent advances in process intensification strategies to improve WCO-based biodiesel production. Pretreatment methods such as heating, filtration, and centrifugation reduce contaminants, while acid esterification lowers FFA before transesterification. The physicochemical properties of WCO, particularly acid value and viscosity, are critical for setting optimal reaction conditions. Catalysts like NaOH (homogeneous), CaO from waste shells (heterogeneous), and bifunctional Mo₇-Zn₃/CaO are widely used to enhance reaction efficiency. Advanced reactors—especially microwave- and ultrasonic-assisted systems—significantly improve yield and energy efficiency. For instance, microwave-assisted transesterification using Mo₇-Zn₃/CaO achieves 94–96% biodiesel yield within 5–10 minutes at65 °C, reducing energy consumption by up to 40% compared to conventional methods. Most approaches meet ASTM D6751 and EN 14214 fuel quality standards. Life cycle assessments show that WCO biodiesel can reduce greenhouse gas emissions by 75–80% compared to fossil diesel. The use of waste-derived catalysts and recycling of by-products such as glycerol supports circular economy goals. Nonetheless, challenges like variable WCO quality and high capital costs for advanced reactors remain. Future work should focus on scalable reactor development, realtime monitoring, and supportive policy frameworks to promote sustainable biodiesel production at an industrial level.